Design of centroid-simplex mixture for the formulation of a high-protein energy bar based on the edible fungus Suillus Luteus (Cuzco-Peru) - Neyra-Benites, Milagros; Rua-Pomahuacre, Silva; Alvites-Ruestas, Walter; Pesantes-Arriola, Genaro; Huamani-Palomino, Wilmer; Brios-Avendaño, Juvencio; Rocha-Fernandez, Victor (LACCEI, 2024)
The dehydrated Suillus luteus fungus from the community of Yuracmayo, the province of Quispicanchi, Cusco. contains high concentrations of proteins. The use of Edible mushroom due to its high protein content promotes healthy products such as energy bars. Through the centroid-simplex mixture design was evaluated using three components for the preparation of an energy bar: (X1: banana, X2: dehydrated mushroom, X3 binder). The variables of response were: Humidity (%), Carbohydrates (%), Ash (%), Fat (%) and Protein (%). The results show that in the 17 experiments, values ​​of Humidity (%), Proteins were obtained (%), Ash (%), Fat (%), Carbohydrates (%) from 4.12 to 70.43, 0.12 to 22.21, 0.32 to 5.53, 0 to 9.6, 29.91 to 88.34, respectively, presenting quadratic and cubic statistical models with values of R2adj greater than 0.99 and p values ​​less than 0.01, indicating a high degree of correlation between experimental values ​​and predicted. The optimal conditions determined by the design are a mixture of 60 to 80% dehydrated Sullius luteus mushroom, banana less than 25% and binder less than 25% to maintain an acceptable protein concentration of 15 to 22% in the bar energy.